Role of endometriosis fertility index system in predicting non-IVF conception in patients with surgically documented endometriosis - T., Fessy Louis; Naveen, Deepa; P., Ramesh; Gopinath, Parasuram; K., Gopinathan K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Endometriosis still remains an enigmatic disease. There are important reasons to stage endometriosis and to prognosticate the chances of pregnancy after a surgical management. The currently used revised AFS system has poor correlation with pregnancy rate. A scoring system-Endometriosis fertility index (EFI) to prognosticate the outcome was proposed few years back. The objective was to assess the usefulness of the EFI system in predicting pregnancy in patients with surgically documented endometriosis who attempt Non-IVF conception. Methods: Retrospective data was collected from 77 subjects with endometriosis who underwent laparoscopy and had documented least function (LF) score and EFI score. All were followed up until 12 months for the occurrence of a non IVF pregnancy. Results: Our study showed that the pregnancy rate was clearly higher in those with high EFI scores than those with low scores. A score of less than 4 was associated with significantly lower pregnancy rates than those with score above 5 (n=26, pregnancy rate- 11.54%) vs. (n=51, pregnancy rate 50.1%); p = 0.001)). Similarly, the pregnancy rate was significantly lower in those with LF score 1-3 (21.2%) as opposed to those with higher LF scores (p =0.029). Also, sensitivity analysis showed that higher EFI score was significantly associated with higher LF score (P <0.001). Conclusions: EFI is a useful clinical tool that predicts pregnancy with reasonable accuracy after endometriosis surgery. Its use clearly provides reassurance to those patients with good prognosis.